Correlation between T-Wave Alternans and Cardiac Volume Status via Intrathoracic Impedance Measurements - Jose' Dizon; Kathleen Hickey; Hasan Garan (Case Reports in Cardiology)
Introduction. The presence of T-wave alternans (TWA) has been shown to correlate with a higher risk for sudden cardiac death. The mechanism of TWA may be related to abnormalities in intracellular calcium handling, which is a mechanism in heart failure and associated arrhythmias as well. However, an association between TWA and cardiac volume status has not been demonstrated. Methods Used. We report the case of a 54-year-old man with a dilated cardiomyopathy who had a biventricular defibrillator system implanted with intrathoracic impedance measurement capability. We performed baseline TWA testing, which was normal and was associated with normal clinical status and normal intrathoracic impedance. We followed intrathoracic impedance measurements, and when the measurement suggested volume overload eight months later, we repeated the TWA test. TWA was grossly positive, and volume overload was corroborated with clinical heart failure. The patient was diuresed, and when clinical status and intrathoracic impedance returned to normal a month later, we repeated TWA, which was again negative. Conclusion. This case demonstrates a correlation between cardiac volume status, as measured by intrathoracic impedance measurements, and TWA status. This data suggests that conditions of volume overload such as heart failure could be causally related to increased TWA, perhaps by the common mechanism of altered intracellular calcium handling.